Corrosion and scale inhibitor, its preparation method and application
By using a specific ratio of glutamic acid and tryptophan to modify polyaspartic acid, the problem of the single functional group of polyaspartic acid grafted with a single amino acid is solved. This achieves a synergistic effect of high-efficiency corrosion inhibition and scale inhibition, and is an environmentally friendly technology that can be applied in the fields of polymer modification and scale inhibitors.
Patent Information
- Application Number
- CN202611166862.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-11-03
AI Technical Summary
In existing technologies, the functional groups of single amino acid grafted polyaspartic acid are limited, making it difficult to simultaneously achieve both corrosion inhibition and scale inhibition performance. Furthermore, traditional corrosion and scale inhibitors contain elements that are harmful to the environment, failing to meet environmental protection requirements.
By using a specific ratio of glutamic acid and tryptophan-modified polyaspartic acid, a coating layer is formed through the synergistic effect of the side chain carboxyl groups of glutamic acid-modified polyaspartic acid and the indole groups of tryptophan-modified polyaspartic acid, thereby achieving a synergistic enhancement of corrosion inhibition and scale inhibition performance.
In industrial water treatment systems, it achieves highly efficient corrosion and scale inhibition performance, with a corrosion inhibition rate of 82.5% and a scale inhibition rate of 56.0%, while meeting environmental protection requirements and exhibiting good biodegradability.
Smart Images

Figure CN123026322A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer modification and scale inhibitor technology, specifically to a corrosion and scale inhibitor, its preparation method, and its application. Background Technology
[0002] In industrial circulating cooling water systems, corrosion of metal equipment and scaling on heat exchange surfaces are key factors restricting the long-term safe operation of the system. Currently, adding chemical agents is the main method to inhibit corrosion and scaling. Polyaspartic acid (PASP), as an environmentally friendly polymer, is widely used as a green scale inhibitor and dispersant due to its biodegradability and non-toxicity.
[0003] To improve the performance of PASP, existing technologies often employ amino acid grafting modification. However, single-amino acid-modified polyaspartic acid has the limitation of a single type of functional group, making it difficult to simultaneously achieve high-efficiency corrosion inhibition and scale inhibition properties in practical applications. Furthermore, some traditional corrosion and scale inhibitors contain environmentally harmful elements such as phosphorus and zinc, which no longer meet increasingly stringent environmental emission standards.
[0004] Therefore, there is an urgent need to develop a green corrosion and scale inhibitor that can combine excellent corrosion inhibition and scale inhibition properties. Summary of the Invention
[0005] This invention provides a corrosion and scale inhibitor, its preparation method, and its application, to solve the problems of single amino acid grafted polyaspartic acid functional groups and unsatisfactory synergistic effect of corrosion inhibition and scale inhibition in related technologies.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a corrosion and scale inhibitor comprising glutamic acid-modified polyaspartic acid and tryptophan-modified polyaspartic acid, wherein the mass ratio of the glutamic acid-modified polyaspartic acid to the tryptophan-modified polyaspartic acid is (0.25-4):1.
[0007] In some embodiments, the mass ratio of the glutamic acid-modified polyaspartic acid to the tryptophan-modified polyaspartic acid is (0.25-1.5):1.
[0008] In some embodiments, the glutamic acid-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of glutamic acid and polysuccinimide, wherein side chain carboxyl groups derived from glutamic acid are grafted onto its molecular chain.
[0009] In some embodiments, the tryptophan-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of tryptophan and polysuccinimide, wherein indole groups derived from tryptophan are grafted onto its molecular chain.
[0010] Secondly, the present invention provides a method for preparing the aforementioned corrosion and scale inhibitor, comprising the following steps: Preparation of glutamic acid-modified polyaspartic acid; Preparation of tryptophan-modified polyaspartic acid; The glutamic acid-modified polyaspartic acid and the tryptophan-modified polyaspartic acid were mixed at a mass ratio of (0.25-4):1 to obtain the corrosion and scale inhibitor.
[0011] In some embodiments, the steps for preparing glutamic acid-modified polyaspartic acid include: dissolving polysuccinimide in a solvent, adding glutamic acid solution, reacting at 40°C for 2-5 hours, adjusting the pH to 7 to precipitate the product, purifying and drying to obtain glutamic acid-modified polyaspartic acid.
[0012] In some embodiments, the steps for preparing tryptophan-modified polyaspartic acid include: dissolving polysuccinimide in a solvent, adding tryptophan solution, reacting at 40°C for 2-5 hours, adjusting the pH to 7 to precipitate the product, purifying and drying to obtain tryptophan-modified polyaspartic acid.
[0013] Thirdly, the present invention provides an application of the aforementioned corrosion and scale inhibitor in an industrial water treatment system.
[0014] In some embodiments, the concentration of the corrosion and scale inhibitor added to the industrial water treatment system is 20-200 mg / L.
[0015] In some embodiments, the industrial water treatment system includes a circulating cooling water system.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: The corrosion and scale inhibitor provided by this invention achieves a synergistic effect of corrosion inhibition and scale inhibition performance through a specific ratio of glutamic acid-modified polyaspartic acid and tryptophan-modified polyaspartic acid. Electrochemical impedance spectroscopy results show that when the mass ratio of the two is 2:3, the charge transfer resistance (Ro) of the system is significantly reduced. ct The corrosion inhibition rate reached its maximum value, at which point the corrosion inhibition rate measured by electrochemical impedance spectroscopy was 82.5%, the corrosion inhibition rate verified by potentiodynamic polarization curve was 78.1%, and the scale inhibition rate at 80℃ standard solution was 56.0%. Compared with other compounding ratios such as 0:5, 1:4, 3:2, 4:1, and 5:0, this ratio showed the best overall performance, proving that the two components formed a complementary coating layer at the microscopic interface, producing a nonlinear synergistic effect.
[0017] In specific applications, this corrosion and scale inhibitor demonstrated highly effective protective capabilities. At 25°C, in a 1 M HCl solution, and with an addition dose of 200 mg / L, it achieved a 79.7% inhibition rate against weight loss corrosion of 304 stainless steel, indicating excellent corrosion stability even in strongly acidic media. In simulated high-concentration circulating water at 40°C and with an addition dose of 200 mg / L, the scale inhibition rate reached 96.3%, approximately 25 percentage points higher than commercially available unmodified polyaspartic acid (72.5%), effectively suppressing scale growth.
[0018] Furthermore, this invention is based on the synthesis of amino acids and polyaspartic acid, and the product has good biodegradability, which meets environmental protection requirements, thus achieving a balance between efficient water treatment and a green environment. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 The adsorption configurations of GP and TP on the Fe(110) crystal plane are shown.
[0021] Figure 2 The adsorption configurations of GP and TP on the calcite (104) crystal plane are shown.
[0022] Figure 3 The adsorption configuration of GP-TP on the Fe (110) crystal plane and the calcite (104) crystal plane of Example 1 is shown.
[0023] Figure 4 The figure shows the results of molecular dynamics simulation of GP-TP on the Fe(110) surface in a corrosive solution.
[0024] Figure 5 is the radial distribution function of GP-TP molecules adsorbed on the Fe(110) surface.
[0025] Figure 6 The figure shows the results of molecular dynamics simulation of GP-TP on the surface of calcite (104) in a corrosive solution.
[0026] Figure 7 The following are the proton nuclear magnetic resonance (NMR) spectra: (a) Comparative Example 1, (b) GP in Example 1, and (c) TP in Example 1.
[0027] Figure 8 Electrochemical impedance spectroscopy of 304 stainless steel in 1 M HCl with different proportions of GP-TP.
[0028] Figure 9 (a) Polarization resistance and (b) corrosion inhibition rate of 304 stainless steel in 1 M HCl with different proportions of GP-TP.
[0029] Figure 10 The potentiodynamic polarization curves of 304 stainless steel in 1 M HCl with different proportions of GP-TP are shown.
[0030] Figure 11 The corrosion inhibition rate was calculated for the self-corrosion current density of 304 stainless steel in 1 M HCl with different proportions of GP-TP.
[0031] Figure 12 The scale inhibition rates of different proportions of GP-TP in standard solutions at 80°C.
[0032] Figure 13 (a): Weight loss diagram; (b): Weight loss corrosion inhibition diagram. 304 was soaked in 1 M HCl with different proportions of GP-TP for 24 h at 25°C.
[0033] Figure 14 The scale inhibition rate of GP-TP at different concentrations in simulated water at 40°C and 60°C is shown. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0035] This invention provides a corrosion and scale inhibitor, its preparation method, and its application, to solve the problems of single amino acid grafted polyaspartic acid functional groups and unsatisfactory synergistic effect of corrosion inhibition and scale inhibition in related technologies.
[0036] In a first aspect, the present invention provides a corrosion and scale inhibitor (simplified as GP-TP). According to an embodiment of the present invention, the corrosion and scale inhibitor comprises glutamic acid modified polyaspartic acid (abbreviated as GP) and tryptophan modified polyaspartic acid (abbreviated as TP), wherein the mass ratio of the glutamic acid modified polyaspartic acid to the tryptophan modified polyaspartic acid is (0.25-4):1.
[0037] This invention achieves a synergistic effect of corrosion inhibition and scale inhibition by combining glutamic acid-modified polyaspartic acid and tryptophan-modified polyaspartic acid in a specific mass ratio, utilizing the differences in their functional groups. Tryptophan-modified polyaspartic acid, with its strong adsorption properties of indole groups, forms an adsorption film on the metal surface, primarily undertaking the corrosion inhibition function; while glutamic acid-modified polyaspartic acid, with its abundant side-chain carboxyl groups, chelates and disperses scale ions, primarily undertaking the scale inhibition function. Furthermore, within a mass ratio range of (0.25-4):1, the indole groups provided by TP are sufficient to form a continuous coating layer on the metal surface, while the carboxyl groups provided by GP can fully chelate and disperse scale ions. The two components complement each other at the microscopic interface, avoiding adsorption site competition or steric hindrance effects caused by excessive amounts of a single component, thus achieving the optimal match between corrosion inhibition and scale inhibition performance.
[0038] The performance of the corrosion and scale inhibitor of this invention is closely related to its adsorption configuration and adsorption strength on the surface of metal and scale. Figure 1 The lowest energy adsorption configurations of GP and TP on the Fe(110) crystal plane are shown. As can be seen from the figure, GP and TP molecules adsorb on the Fe(110) crystal plane in an approximately parallel manner, forming a large area of coverage on the substrate surface. This adsorption configuration maximally hinders the diffusion of corrosive ions into the substrate. The adsorption energies of GP and TP molecules can be calculated from Monte Carlo simulation results, mainly consisting of rigid adsorption energy and deformation energy, as shown in Table 1.
[0039] Table 1 Monte Carlo simulation data of GP and TP on the Fe(110) crystal plane
[0040] Table 1 shows that the negative adsorption energies of both GP and TP indicate that the adsorption of the two molecules on the Fe(110) crystal plane is spontaneous, and TP has a more negative adsorption energy, indicating that the adsorption of TP on the Fe(110) crystal plane is more compact. The deformation energy indicates that the two molecules underwent some deformation during adsorption, and the deformation of TP was greater. This is because the indole groups in TP are adsorbed approximately parallel to the Fe(110) crystal plane, forming a relatively stable adsorption structure, which leads to a certain degree of molecular deformation.
[0041] Furthermore, Figure 2 The adsorption configurations of GP and TP on the calcite (104) crystal face are shown. It can be seen that GP is adsorbed approximately parallel to the calcite surface, mainly due to the adsorption of carboxyl and amide groups onto the surface. The adsorption of TP on the calcite (110) crystal face has a slightly smaller coverage area compared to the Fe (110) crystal face, because the indole groups form an angle with the calcite surface, while the carboxyl and some amide groups are closer to the calcite surface. This indicates that GP-TP mainly interacts with the calcite (104) crystal face through the interaction of carboxyl and amide groups.
[0042] Table 2 shows the adsorption energy data of GP and TP in Monte Carlo simulations on the calcite (104) crystal plane. The specific data are shown in Table 2.
[0043] Table 2 Monte Carlo simulation data of GP and TP on the calcite (104) crystal face.
[0044] Comparing Tables 1 and 2, it can be seen that the absolute values of the adsorption energies of GP and TP on the calcite surface are both lower than their adsorption energies on the Fe (110) crystal plane, indicating that their adsorption capacity on the calcite surface is weaker than their adsorption capacity on the iron surface. The deformation energy indicates that GP and TP underwent certain deformation during the adsorption process. The adsorption energy of GP on the calcite (104) crystal plane is more negative than that of TP, indicating that GP has a better adsorption capacity on the calcite surface.
[0045] In some embodiments of the present invention, the mass ratio of the glutamic acid-modified polyaspartic acid to the tryptophan-modified polyaspartic acid is (0.25-1.5):1. Preferably, the mass ratio is 2:3. At this specific ratio, the corrosion inhibition and scale inhibition effects of the two modified polymers achieve the best balance, and the synergistic effect is most significant.
[0046] Based on the optimal blending ratio of 2:3, Monte Carlo simulations were performed on the GP-TP blending system on the Fe (110) and calcite (104) crystal planes, respectively. The simulation results are as follows: Figure 3 As shown. Due to the periodic structure of the crystal lattice, the fact that some atoms extend beyond the lattice does not affect the simulation results. From the adsorption configuration, it can be seen that there is no mutual interference in the adsorption between molecules. The adsorption of GP-TP after compounding is similar to that when it is independent. GP is flatly adsorbed on both the Fe (110) and calcite (104) crystal planes, mainly by amide and carboxyl groups. TP exhibits a flatter adsorption configuration on the Fe (110) crystal plane, with indole groups almost parallel to the surface, while on the calcite (104) crystal plane, it is mainly by amide and carboxyl groups, with indole groups at a certain angle to the surface.
[0047] Table 3 shows the adsorption energy data of GP-TP in Monte Carlo simulations on Fe (110) and calcite (104) crystal planes. The specific data are shown in Table 3.
[0048] Table 3 Monte Carlo simulation data of GP-TP in Fe (110) and calcite (104) crystal planes at a 2:3 ratio.
[0049] As shown in Table 3, the negative adsorption energy indicates that GP-TP can spontaneously adsorb on the Fe(110) and calcite(104) crystal planes, with a tighter adsorption on the Fe(110) crystal plane. The rigid adsorption energy indicates that the GP-TP molecules underwent a certain deformation during the adsorption process. Furthermore, the differential adsorption energies of GP and TP were calculated separately. The results show that GP and TP have better adsorption capabilities on the calcite(104) and Fe(110) crystal planes, respectively, and the differential adsorption energies are all greater than those of GP and TP when adsorbed individually. This indicates that the compound further improves the adsorption capacity of GP-TP on the substrate and scale layer.
[0050] In summary, Monte Carlo simulation results confirm that GP and TP have better adsorption capabilities on the surfaces of calcite (110) and Fe (110), respectively. This verifies the effectiveness of selecting GP and TP as scale inhibitors and corrosion inhibitors, respectively, while both exhibiting both corrosion inhibition and scale inhibition effects, demonstrating a good synergistic effect. TP mainly relies on indole and amide groups to achieve adsorption on the Fe (110) surface, and the near-parallel adsorption mode can effectively hinder the diffusion of corrosive ions into the matrix. GP mainly relies on carboxyl and amide groups to achieve adsorption on the calcite (110) surface. Tight adsorption can lead to lattice distortion, affecting scale growth. In general, GP-TP preferentially adsorbs on the Fe (110) surface, forming a tighter adsorption and larger coverage area. Meanwhile, the carboxyl and amide groups of GP-TP also have a certain adsorption capacity on the calcite (110) surface, interfering with the normal growth of the scale layer and thus achieving the effect of scale inhibition.
[0051] In some embodiments of the present invention, the glutamic acid-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of glutamic acid and polysuccinimide, wherein side chain carboxyl groups derived from glutamic acid are grafted onto its molecular chain.
[0052] Through a ring-opening grafting reaction between glutamic acid and polysuccinimide, the unique side-chain carboxyl groups of glutamic acid are stably introduced into the molecular backbone of polyaspartic acid. The introduced high-density carboxyl groups possess excellent chelating and dispersing capabilities, effectively capturing scale-forming ions such as calcium and magnesium in water and interfering with the normal growth lattice of scale crystals, thereby enhancing the scale inhibition performance of the corrosion and scale inhibitor. Simultaneously, the chemical grafting method ensures the stability and durability of the functional groups during water treatment, avoiding the drawback of easy loss of free amino acids, and providing a solid foundation for the synergistic effect of corrosion inhibition and scale inhibition in the compound system.
[0053] In some embodiments of the present invention, the tryptophan-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of tryptophan and polysuccinimide, wherein indole groups derived from tryptophan are grafted onto its molecular chain.
[0054] The indole group, unique to tryptophan, is stably introduced into the polyaspartic acid molecular chain via a ring-opening grafting reaction. Due to the large π-bond structure of the indole group, the modified polymer can undergo strong physical or chemical adsorption with the metal surface, forming a dense and stable adsorption film. This adsorption film effectively blocks the contact between the corrosive medium and the metal substrate, thus improving the corrosion inhibition performance of the system. Simultaneously, the chemical grafting method overcomes the drawback of free additives being easily lost, ensuring the persistence of the corrosion-inhibiting functional groups during water treatment, and providing crucial corrosion inhibition functional support for the synergistic effect of corrosion inhibition and scale inhibition in the compound system.
[0055] Secondly, the present invention provides a method for preparing the aforementioned corrosion and scale inhibitor. According to an embodiment of this application, the preparation method includes the following steps: S100: Preparation of glutamic acid modified polyaspartic acid.
[0056] In this step, glutamic acid modified polyaspartic acid is prepared. Specifically, polysuccinimide is dissolved in a solvent, glutamic acid solution is added, and the mixture is reacted at 40°C for 2-5 hours. The pH value is adjusted to precipitate the product, which is then purified and dried to obtain glutamic acid modified polyaspartic acid.
[0057] S200: Preparation of tryptophan-modified polyaspartic acid.
[0058] In this step, tryptophan-modified polyaspartic acid is prepared. Specifically, polysuccinimide is dissolved in a solvent, glutamic acid solution is added, and the mixture is reacted at 40°C for 2-5 hours. The pH value is adjusted to precipitate the product, which is then purified and dried to obtain tryptophan-modified polyaspartic acid.
[0059] S300: Compound mixture.
[0060] In this step, the glutamic acid-modified polyaspartic acid obtained in step S100 and the tryptophan-modified polyaspartic acid obtained in step S200 are mixed at a mass ratio of (0.25-4):1 to obtain the corrosion and scale inhibitor. By controlling the compounding ratio of the two, the relative content of carboxyl and indole groups in the agent can be adjusted to meet the corrosion and scale inhibition requirements under different water quality conditions.
[0061] Thirdly, this invention provides an application of the aforementioned corrosion and scale inhibitor in an industrial water treatment system. By adding this corrosion and scale inhibitor to the industrial water treatment system, the problem that existing water treatment agents cannot simultaneously achieve corrosion inhibition and scale inhibition performance under complex water quality conditions can be effectively solved.
[0062] To further elucidate the mechanism of action of this corrosion and scale inhibitor, this invention uses molecular dynamics simulations to study the adsorption behavior and interaction between the corrosion and scale inhibitor molecules and the substrate and calcium carbonate in a solution environment. Figure 4The results of molecular dynamics simulations of GP-TP on the Fe(110) crystal surface in a corrosive solution at 25°C show that GP-TP molecules adsorb almost parallel on the metal surface, providing a large coverage and hindering the adsorption and diffusion of corrosive ions on the substrate surface. The indole group of TP provides a larger adsorption area and participates more in the corrosion inhibition effect. The adsorption energy E of GP-TP on the Fe(110) surface is calculated using Equation 1. ads The value was -4723.37 kJ / mol, indicating that the adsorption system is spontaneous and stable, consistent with the results of Monte Carlo simulations.
[0063] Formula 1 In the formula: The total energy of the solid-liquid system is expressed in kJ / mol. The total molecular energy of solids and solutions without corrosion and scale inhibitors, in kJ / mol; The total energy of the corrosion and scale inhibitor molecules is expressed in kJ / mol.
[0064] In a solid-liquid system, the average force potential W(r) can describe the interaction between particles: Formula 2 In the formula, g(r) is the radial distribution function. When attractive interactions dominate at a certain distance, g(r) > 1 and W(r) < 0. Therefore, the distance and interaction force between metal surface atoms and corrosion / scale inhibitor molecules can be determined based on the radial distribution function g(r). Typically, the first peak of the RDF curve in the range of 1 ~ 3.5 Å indicates chemisorption between the two, belonging to short-range adsorption. Figure 5 It can be seen that the first peaks on the RDF curves of GP and TP with metallic Fe are 2.23 Å and 2.29 Å, respectively, indicating that the two corrosion inhibitor molecules have stable chemical adsorption on the Fe(110) surface.
[0065] Figure 6 The figure shows the molecular dynamics simulation results of GP-TP on the surface of calcite (104) in corrosive solution. It can be found that the adsorption effect of TP on the calcite surface is slightly weaker than that on the Fe surface. The indole groups did not adsorb parallel on the calcite surface, and the adsorption was mainly of amide groups. GP, on the other hand, can adsorb on the surface in approximately parallel, indicating that GP can interact more with the scale layer and participate more in the scale inhibition effect.
[0066] In summary, the simulation results reveal the selective adsorption mechanism of the GP-TP composite system at different interfaces: TP mainly relies on the preferential adsorption of indole groups on the metal surface to provide corrosion inhibition protection, while GP mainly relies on the preferential action of carboxyl and amide groups on the scale crystal surface to provide scale inhibition and dispersion. The synergistic effect of the two achieves efficient corrosion inhibition and scale inhibition.
[0067] In some embodiments of the present invention, the concentration of the corrosion and scale inhibitor in the industrial water treatment system is 20-200 mg / L. Within this concentration range, the agent molecules can reach the effective adsorption threshold on the metal surface and scale surface, forming a dense protective film and inhibiting crystal growth, thereby achieving excellent corrosion and scale inhibition performance. If the concentration is below 20 mg / L, it is difficult to form a continuous coating layer, and the protective effect is significantly reduced; if the concentration is above 200 mg / L, the marginal effect of performance improvement decreases, and operating costs and environmental impact increase.
[0068] In some embodiments of the present invention, the industrial water treatment system includes a circulating cooling water system.
[0069] The technical solution provided by the present invention will be described in detail below with reference to the embodiments.
[0070] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available analytical grade materials.
[0071] Example 1 Example 1 of this application provides a corrosion and scale inhibitor, the preparation method of which is as follows: 1. Preparation of glutamic acid-modified polyaspartic acid (GP) 10 g of polysuccinimide (PSI, molecular weight approximately 7000-8000 Da) was dissolved in 100 mL of deionized water. 7.5 g of glutamic acid was added to 50 mL of 10% NaOH solution, followed by slow dropwise addition of the glutamic acid solution to the polysuccinimide solution. The reaction was stirred at 40 °C for 2 hours. After the reaction was complete, the pH of the system was adjusted to 7.0 using 10% HCl solution, and then a large amount of anhydrous ethanol was added to precipitate the product. Unreacted amino acids were removed by dialysis, and the product was freeze-dried to obtain a glutamic acid-modified polyaspartic acid solid powder.
[0072] 2. Preparation of tryptophan-modified polyaspartic acid (TP) 10 g of polysuccinimide (PSI, molecular weight approximately 7000-8000 Da) was dissolved in 100 mL of deionized water. 10 g of tryptophan was added to 50 mL of 10% NaOH solution, followed by slow dropwise addition of the tryptophan solution to the polysuccinimide solution. The reaction was stirred at 40 °C for 2 hours. After the reaction was complete, the pH of the system was adjusted to 7.0 using 10% HCl solution, and then a large amount of anhydrous ethanol was added to precipitate the product. Unreacted amino acids were removed by dialysis, and the product was freeze-dried to obtain tryptophan-modified polyaspartic acid solid powder.
[0073] 3. Preparation of corrosion and scale inhibitors Weigh the glutamic acid-modified polyaspartic acid (GP) prepared in step 1 and the tryptophan-modified polyaspartic acid (TP) prepared in step 2 at a mass ratio of 4:1, place them in a mixing container, add an appropriate amount of deionized water to dissolve them, stir and mix evenly for 30 minutes to obtain the corrosion and scale inhibitor (simplified as GP-TP).
[0074] Example 2 The difference between this embodiment and embodiment 1 is that in step 3, the mixing mass ratio of GP to TP is 3:2.
[0075] Example 3 The difference between this embodiment and embodiment 1 is that in step 3, the mixing mass ratio of GP to TP is 2:3.
[0076] Example 4 The difference between this embodiment and embodiment 1 is that in step 3, the mixing mass ratio of GP to TP is 1:4.
[0077] Comparative Example 1 This comparative example provides unmodified polyaspartic acid (PASP), obtained by direct hydrolysis of PSI, as a control.
[0078] Comparative Example 2 The difference between this comparative example and Example 1 is that in step 3, only the glutamic acid-modified polyaspartic acid (GP) prepared in step 1 is used, and TP is not added.
[0079] Comparative Example 3 The difference between this comparative example and Example 1 is that in step 3, only the tryptophan-modified polyaspartic acid (TP) prepared in step 2 is used, and GP is not added.
[0080] Performance testing 1. Structural characterization The GP and TP obtained in steps 1 and 2 of Example 1, as well as the unmodified polyaspartic acid (PASP) obtained in Comparative Example 1, were characterized by 1H NMR spectroscopy. Spectral results ( Figure 7 The results show that the positions of the characteristic peaks are consistent with the theoretical structure, confirming the successful synthesis of PASP, TP, and GP.
[0081] 2. Corrosion and scale inhibition performance tests of different proportions of GP-TP To investigate the synergistic effect between the corrosion inhibitor and scale inhibitor components and determine the optimal compounding ratio, the performance of samples prepared in Examples 1-4 and Comparative Examples 2-3 was evaluated. During the testing process, the total amount of GP-TP added was controlled at 20 mg / L. 304 stainless steel electrode samples were immersed in 1 M HCl solutions containing different mass ratios of GP-TP, and electrochemical impedance spectroscopy was used to evaluate the corrosion inhibition performance under different compounding ratios.
[0082] Figure 8 The electrochemical impedance spectroscopy results show that the impedance of the system significantly increased after the addition of the corrosion and scale inhibitor, and the peak value of the phase angle also increased, indicating that the corrosion and scale inhibitor has a good corrosion inhibition effect. The phase angle plot of the Bode plot shows a peak, indicating a time constant. The Nyquist plot shows the presence of a capacitive arc, and an inductive arc exists in the low-frequency region, which is related to the active dissolution of the 304 surface and the adsorption and desorption of organic matter. Furthermore, due to the inhomogeneity of the substrate surface, a constant-phase element (CPE) is used instead of an ideal capacitor. Therefore, R... s (CPE(R) ct (RLL))) The equivalent circuit diagram is fitted, where R s R is the resistance of the solution. ct As a charge transfer resistor, CPE is related to R ct Parallel constant-phase elements, where L is the inductance and R is the constant-phase element. L This represents inductance and resistance. The fitting results are shown in Table 4.
[0083] Table 4. Electrochemical impedance fitting parameters of 304 stainless steel in 1 M HCl with different proportions of GP-TP.
[0084] According to the physical meaning of the equivalent circuit diagram, R ct The size can be used to assess the corrosion resistance of the substrate. It was found that after adding corrosion and scale inhibitors, R... ct The significant increase in size indicates that GP-TP has a corrosion inhibition effect on 304. Furthermore, with the increase in R... ct The value of GP:TP first increases and then decreases as GP:TP increases, reaching its maximum when GP:TP is 8:12.
[0085] Calculate the polarization resistance of the system, such as Figure 9 As shown in (a), the polarization resistance of the system increases significantly after the addition of the corrosion and scale inhibitor, and first increases and then decreases with the concentration of GP. The electrochemical impedance retardation rate of GP-TP is calculated using Equation 3. ,like Figure 9 (b) When the GP-TP ratio is 2:3, the optimal corrosion inhibition rate is 82.5%.
[0086] Formula 3 In the formula, Electrochemical impedance retardation rate; The polarization resistance, in Ω, is the value of the added corrosion and scale inhibitor. The polarization resistance without the addition of corrosion and scale inhibitors is Ω.
[0087] Furthermore, under the condition of GP-TP addition of 20 mg / L, the potentiodynamic polarization curves of 304 stainless steel electrode samples in 1 M HCl with different mass ratios of GP-TP were tested, and the results are as follows: Figure 10 After adding the corrosion inhibitor, the self-corrosion potential of 304 did not change significantly, with the difference not exceeding 85 mV, indicating that GP-TP is a mixed corrosion inhibitor. The self-corrosion current density of 304 decreased after adding GP-TP. The corrosion inhibition rates of different proportions of GP-TP were calculated based on the self-corrosion current density. Figure 11 The optimal corrosion inhibition rate of 78.1% was observed when the GP-TP ratio was 2:3. Based on the above results, it is concluded that GP and TP have the best corrosion inhibition efficiency when the compound ratio is 2:3.
[0088] Subsequently, the scale inhibition performance of GP-TP compound agents with different mass ratios was evaluated using the standard solution scale inhibition test method specified in the national standard GB / T 16632-2019 "Determination of Scale Inhibition Performance of Water Treatment Agents - Calcium Carbonate Deposition Method". The test temperature was 80°C. The scale inhibition rate of the GP-TP compound agent was calculated by measuring the volume of EDTA standard solution consumed in the titration and combining it with the following formula.
[0089] The preparation methods for the standard solutions and test solutions used in the experiment are as follows: Add 250 mL of water to a 500 mL volumetric flask, and add a certain volume of calcium chloride standard solution using a burette to make the amount of calcium ions 120 mg. Add a certain amount of water treatment agent sample solution using a pipette and shake well. Then add 20 mL of borax buffer solution and shake well. Slowly add a certain volume of sodium bicarbonate standard solution using a burette (shaking while adding) to make the amount of bicarbonate ions 366 mg, dilute with water to the mark, and shake well. Note that 1 mL of the calcium chloride standard solution contains approximately 6.0 mg of calcium chloride. 2+ Sodium bicarbonate standard solution: 1 mL contains approximately 18.3 mg HCO3. - Borax buffer solution: pH≈9, weigh 3.80g sodium tetraborate decahydrate, dissolve in water and dilute to 1L.
[0090] Based on the titration results, the scale inhibition rate is calculated using formulas 4 and 5: Formula 4 In the formula: V1 is the volume of EDTA standard solution consumed in the titration, mL; c is the EDTA concentration, mol / L; M is the Ca2+ concentration. 2+ Molar mass, 40.08 g / mol; V is the volume of test solution used in the titration, 25 mL; Formula 5 In the formula: ρ1 is the Ca before the solution test. 2+ Concentration, mg / mL; ρ2 is the Ca2+ concentration after the blank solution test.2+ Concentration, mg / mL; ρ3 is the Ca content of the solution after adding corrosion and scale inhibitors in the test. 2+ Concentration, mg / mL; Test results of GP-TP scale inhibition rate under different compounding ratios are as follows: Figure 12 As shown, it can be found that the scale inhibition rate first increases and then decreases with the mass fraction of GP, and the best scale inhibition rate of 56.0% is achieved when the GP-TP ratio is 2:3.
[0091] In summary, based on the experimental results of different compounding ratios for corrosion and scale inhibition, it is believed that GP-TP at a ratio of 2:3 has the best corrosion and scale inhibition efficiency, and the compounding ratio of GP-TP corrosion and scale inhibitors used thereafter is 2:3.
[0092] 3. The corrosion inhibition performance of the GP-TP obtained in Example 1 was tested. 304 stainless steel was immersed in 1 M HCl solutions containing different concentrations of GP-TP for 24 h at 25°C, followed by weight loss and surface characterization. Weight loss and corrosion inhibition rates are shown below. Figure 13 The results showed that the weight loss of 304 stainless steel decreased significantly after the addition of GP-TP. The corrosion rate of 304 was calculated using Equation 6, and the corrosion inhibition rate was then calculated using Equation 7. The corrosion inhibition rate increased with increasing GP-TP concentration, and the increase in corrosion inhibition rate tended to plateau when the addition amount reached 200 mg / L, with the corrosion inhibition rate reaching 79.7%. This indicates that GP-TP has good corrosion inhibition performance for 304 stainless steel in 1 M HCl.
[0093] Formula 6 In the formula: The corrosion rate is expressed in mm / a. The weight loss of the sample is expressed in g. The density of the sample is in g / cm³. 3 ; The test area is in cm². 2 ; The test time is in hours (h).
[0094] The corrosion and scale inhibition rates of different test groups were calculated using Equation 7: Formula 7 In the formula: The corrosion inhibition rate due to weight loss; Corrosion rate without the addition of corrosion and scale inhibitors, mm / a; The corrosion rate is measured in mm / a when corrosion and scale inhibitors are added.
[0095] 4. Scale inhibition performance test of the GP-TP obtained in Example 1. To further evaluate the applicability of the GP-TP compound prepared in Example 1 in real complex water environments, this test referenced water quality data from actual industrial circulating water systems and prepared highly concentrated simulated circulating water for scale inhibition performance evaluation.
[0096] Based on actual water environment data from an industrial heat exchange system (see Table 5), particularly the ionic composition characteristics of the circulating water after 20 days of concentration, a highly concentrated simulated circulating water with a high scaling tendency was prepared. To accelerate the evaluation of the limiting performance of the scale inhibitor, the concentration of key scale-forming ions in the simulated water was enhanced; specific solute ion concentration parameters are shown in Table 6. When preparing the solution, different concentrations of corrosion and scale inhibitors and a certain amount of boric acid buffer solution were added before adding sodium bicarbonate. The solution was then heated in a water bath at 40°C and 60°C for 10 h. Changes in calcium ion concentration were detected by titration, and differences in scale phase were detected using XRD.
[0097] Table 5 Water environment data (heat exchanger makeup water and concentrated water after 20 days of circulation)
[0098] Table 6 Ion Concentration Parameters of Highly Concentrated Simulated Circulating Water
[0099] The scale inhibition rate calculated based on Equations 4 and 5 above is as follows: Figure 14 As shown, the scale inhibition rate of GP-TP increases with increasing concentration, but the increase slows down when the GP-TP addition reaches 100 mg / L. The scale inhibition rate decreases slightly with increasing temperature, but remains at a high level. At 40°C, adding 200 mg / L GP-TP achieves a scale inhibition rate of 96.3%. In contrast, the scale inhibition rate of commercially available unmodified PASP is only 72.5%, indicating that GP-TP's scale inhibition rate is 25% higher. This demonstrates that GP-TP has a certain chelating and solubilizing effect in simulated water and exhibits excellent scale inhibition performance against calcium carbonate scale.
[0100] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.
[0101] It should be noted that in this invention, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, technology, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, technology, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, technology, article, or apparatus that includes said element. In this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.
[0102] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features of the invention herein.
Claims
1. A corrosion and scale inhibitor, characterized in that, It includes glutamic acid-modified polyaspartic acid and tryptophan-modified polyaspartic acid, wherein the mass ratio of the glutamic acid-modified polyaspartic acid to the tryptophan-modified polyaspartic acid is (0.25-4):
1.
2. The corrosion and scale inhibitor as described in claim 1, characterized in that, The mass ratio of the glutamic acid-modified polyaspartic acid to the tryptophan-modified polyaspartic acid is (0.25 - 1.5):
1.
3. The corrosion and scale inhibitor as described in claim 1 or 2, characterized in that, The glutamic acid-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of glutamic acid and polysuccinimide, and its molecular chain is grafted with side chain carboxyl groups derived from glutamic acid.
4. The corrosion and scale inhibitor as described in claim 1 or 2, characterized in that, The tryptophan-modified polyaspartic acid is a polymer obtained by ring-opening grafting reaction of tryptophan and polysuccinimide, and its molecular chain is grafted with indole groups derived from tryptophan.
5. A method for preparing a corrosion and scale inhibitor as described in any one of claims 1-4, characterized in that, Includes the following steps: Preparation of glutamic acid-modified polyaspartic acid; Preparation of tryptophan-modified polyaspartic acid; The glutamic acid-modified polyaspartic acid and the tryptophan-modified polyaspartic acid were mixed at a mass ratio of (0.25-4):1 to obtain the corrosion and scale inhibitor.
6. The preparation method according to claim 5, characterized in that, The steps for preparing glutamic acid-modified polyaspartic acid include: dissolving polysuccinimide in a solvent, adding glutamic acid solution, reacting at 40℃ for 2-5 hours, adjusting the pH value to precipitate the product, purifying and drying to obtain glutamic acid-modified polyaspartic acid.
7. The preparation method according to claim 5, characterized in that, The steps for preparing tryptophan-modified polyaspartic acid include: dissolving polysuccinimide in a solvent, adding tryptophan solution, reacting at 40℃ for 2-5 hours, adjusting the pH value to precipitate the product, purifying and drying to obtain tryptophan-modified polyaspartic acid.
8. The application of a corrosion and scale inhibitor as described in any one of claims 1-4 in an industrial water treatment system.
9. The application as described in claim 8, characterized in that, The concentration of the corrosion and scale inhibitor in the industrial water treatment system is 20-200 mg / L.
10. The application as described in claim 8, characterized in that, The industrial water treatment system includes a circulating cooling water system.
